1999
DOI: 10.1007/pl00006609
|View full text |Cite
|
Sign up to set email alerts
|

PCDD/F Levels in the Vicinity of an Old Municipal Solid Waste Incinerator: Temporal Variation in Soils

Abstract: In order to determine the temporal variation in the levels of polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) in soils in the vicinity of an old municipal solid waste incinerator (Montcada, Barcelona, Spain), in 1997 we collected 24 soil samples at the same sampling points in which samples were taken 1 year before. Each sample was analyzed for PCDDs and PCDFs by GC/MS. While in the previous study PCDD/F concentrations ranged from 0.30 to 44.26 ng TEQ/kg (dry matter), (median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although studies carried out in Spain (9,29) did not demonstrate any significant difference in PCDD/F levels in soils according to wind direction, Maincy's soils, which were situated under the prevailing wind direction showed significantly higher PCDD/F levels than comparison soils. Soil from site 10 which was located close to the MSWI in a Northerly direction showed dioxin levels which were markedly lower than other soils from the study area situated Northeast, proving the probable strong influence of wind direction.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although studies carried out in Spain (9,29) did not demonstrate any significant difference in PCDD/F levels in soils according to wind direction, Maincy's soils, which were situated under the prevailing wind direction showed significantly higher PCDD/F levels than comparison soils. Soil from site 10 which was located close to the MSWI in a Northerly direction showed dioxin levels which were markedly lower than other soils from the study area situated Northeast, proving the probable strong influence of wind direction.…”
Section: Discussionmentioning
confidence: 84%
“…However, it has been found that PCBs are also emitted from industrial sources, even if they weakly contribute to total TEQ ( , ). Because soils have been demonstrated to act as a conservative matrix for dioxin or PCB atmospheric deposition and to reflect a long-term exposure (), the impact of pollution from these old factories would still be perceptible in the surrounding grounds ( , ). Foraging animals such as free-range chickens are particularly exposed to soil contamination by direct soil ingestion.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, although recent studies have demonstrated that for MSWI with modern technologies, human PCDD/F exposure is mainly due to background contamination (Domingo, 2002;Domingo et al, 1999bDomingo et al, , 2002, there are only a few reports concerning PCDD/F concentrations in blood of subjects living in the vicinity of MSWIs. Deml et al (1996) did not find direct health hazards related to PCDD/F emissions from a German MSWI.…”
Section: Levels Of Dioxins and Furans Agramunt Et Almentioning
confidence: 99%
“…The damaging effects of dust fall, is characterized by enriched toxic heavy metals such as As, Pb, Ni, Cr, Cu, Zn, Mn and Cd [27,28]. While some of these elements are essential for humans, at high levels they can also mean a toxicological risk [25,29].…”
Section: Discussionmentioning
confidence: 99%